Lung transplant waitlist mortality: Height as a predictor of poor outcomes. (19th November 2014) - Keeshan, Britton C.; Rossano, Joseph W.; Beck, Nicole; Hammond, Rachel; Kreindler, James; Spray, Thomas L.; Fuller, Stephanie; Goldfarb, Samuel
Abstract: The LAS was designed to minimize pretransplant mortality while maximizing post‐transplant outcome. Recipients <12 are not allocated lungs based on LAS. Waitlist mortality has decreased for those >12, but not <12, suggesting this population may be disadvantaged. To identify predictors of waitlist mortality, a retrospective analysis of the UNOS database was performed since implementation of the LAS. There were 16 973 patients listed for lung transplant in the United States; 12 070 (71.1%) were transplanted, and 2498 (14.7%) patients died or were removed from the wait list. Significantly more pediatric patients died or were removed compared with adults (22.0% vs. 14.4%, p < 0.01). In multivariate analysis, in addition to higher LAS at time of listing (adj. HR1.058, 1.055–1.060), shorter height (1.008, 1.006–1.010), male gender (1.210, 1.110–1.319), and requiring ECMO (1.613, 1.202–2.163) were associated with pretransplant mortality. Post‐transplant survival was not affected by height. The current age cutoff may impose limitations within the current lung allocation system in the United States. Height is an independent predictor of waitlist mortality and may be a valuable factor for the development of a comprehensive lung allocation system.